Democracy in one book or less : how it works, why it doesn't, and why fixing it is easier than you think - Litt, David, 1986- (Ecco, an imprint of HaperCollinsPublishers, 2020)
Here's something true for almost every American. The democracy you live in today is different, completely different, than the democracy born into. Since 1980, the number of Americans legally barred from voting has more than doubled. Since the 1990s, odds of living in a competitive Congressional district have fallen by more than half. In the twenty-first century alone, the amount of money spent on Washington lobbying has increased by more than 100 percent. Meanwhile, new rules in Congress make passing new bills nearly impossible, no matter how popular or bipartisan they are. No wonder it feels like representatives have stopped representing the people. Millions of Americans now recognize that democracy is in trouble and that the trouble goes beyond Trump. But too often, they are looking in the wrong places for solutions. Voter suppression is real, but Voter ID laws aren't tipping elections. Getting rid of bizarrely shaped districts won't end gerrymandering.